Gender Concepts in the Phraseological World Picture of the English and Uzbek Languages (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
A new interpretation of the processes of categorization within the framework of cognitive linguistics, refusal to recognize the objective truth, interest in the subjective and private life of a person, the development of new theories of personality, in particular, the theory of social constructivism, led to a revision of the scientific principles of studying the categories of sex, previously interpreted mainly as biologically deterministic. These facts have led to the emergence of a number of scientific disciplines focused on the study of the socio-cultural construction of various aspects of social identity, including gender. The linguistic expression of stereotypes in the form of phraseological units seems to us the most vivid reflection of the cultural potential of the nation, since, interpreted by most researchers as "representatives of the national mentality", they are "a means of expressing the essence of the conceptual structure of ethnocultural consciousness." Gender stereotypes that embody the concepts of "masculinity" and "femininity", in turn, determine the models of social behavior, being part of the conceptual and linguistic picture of the world.